2018
DOI: 10.1074/jbc.ra117.001167
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 expression mediated by calcium-TonEBP signaling axis under hyperosmotic conditions serves osmoprotective function in nucleus pulposus cells

Abstract: The nucleus pulposus (NP) of intervertebral discs experiences dynamic changes in tissue osmolarity because of diurnal loading of the spine. TonEBP/NFAT5 is a transcription factor that is critical in osmoregulation as well as survival of NP cells in the hyperosmotic milieu. The goal of this study was to investigate whether cyclooxygenase-2 (COX-2) expression is osmoresponsive and dependent on TonEBP, and whether it serves an osmoprotective role. NP cells up-regulated COX-2 expression in hyperosmotic media. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…TNFα may be involved in maintaining cell viability and matrix homeostasis in the physiologically challenging disc niche that is hypoxic, hyperosmolar, and under mechanical stress . Earlier work from our group found that TNFα expression is maintained in the postnatal NP cells by tonicity‐responsive binding‐protein (TonEBP); this transcription factor controls cell adaptive responses in the hyperosmolar disc environment likely in part by regulating the expression of pro‐survival and anabolic matrix genes . Additionally, complete removal of IL‐1β, another cytokine closely related to disc degeneration, renders mice more susceptible to age‐related disc degeneration, further reinforcing the importance of the physiological role that certain cytokines play in the preservation of disc health .…”
Section: Discussionmentioning
confidence: 99%
“…TNFα may be involved in maintaining cell viability and matrix homeostasis in the physiologically challenging disc niche that is hypoxic, hyperosmolar, and under mechanical stress . Earlier work from our group found that TNFα expression is maintained in the postnatal NP cells by tonicity‐responsive binding‐protein (TonEBP); this transcription factor controls cell adaptive responses in the hyperosmolar disc environment likely in part by regulating the expression of pro‐survival and anabolic matrix genes . Additionally, complete removal of IL‐1β, another cytokine closely related to disc degeneration, renders mice more susceptible to age‐related disc degeneration, further reinforcing the importance of the physiological role that certain cytokines play in the preservation of disc health .…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, we decided to investigate the role of p38 MAPK on the regulation of DGATs at the mRNA level. We used a small molecule inhibitor SB‐202190, which inhibits p38 MAPKα and p38 MAPKβ, and investigated the effect of p38 MAPK inhibition on DGAT1 expression during apoptosis. We collected control, SB‐202190‐treated, 5‐FU‐treated and 5‐FU+SB‐202190‐treated cells, and measured the expression of genes of interest in these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…54 In addition, the induction of COX-2 is dependent on elevation of intracellular calcium levels in nucleus pulposus cells under hyperosmotic conditions. 55 Calcium activation of tonicity-responsive enhancer binding protein (TonEBP) is required for regulation of COX-2 in nucleus pulposus cells. We then examined whether elevated Ca 2+ was responsible for the upregulation of COX-2.…”
Section: Chelation Of Intracellular Calcium Decreases Cox-2 Expressmentioning
confidence: 99%